The Effect of Hydroxyapatite on Alveolar Bone Regeneration in Various Dental Procedure: Systematic Review and Meta-Analysis - Anitasari, Silvia; Belem, Wendimi Fatimala; Wahab, Deasy Evriyani (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
Background. The effect of hydroxyapatite (HA) bone substitute on alveolar bone regeneration has been analyzed in various dental procedures including ridge preservation, sinus augmentation, and periodontal bone defect treatment. The objective on this study was to determine and analyze the structural effect of the HA bone substitute in these dental applications. Methods. The systematic review was conducted using electronic databases from PUBMED, EMBASE, and COCHRANE. The search covered articles published from 1998 up to November 2023. The primary outcome measures were radiographic (intraoral periapical, CT long cone-paralleling technique, computer-assisted densitometry image analysis), histologic/histomorphometry, and other radiographic methods. The secondary outcome measures related to bone regeneration were assessed, including clinical, radiographic/histologic, and histological evaluations. Conclusion. The present systematic review focused on randomized controlled trials (RCTs) and prospective controlled clinical trials (CCTs). The results showed that HA and ß-TCP were found to be safe and clinically acceptable compared to other treatments.